Resiliensi Mata Pencaharian Peternak Ayam Broiler di Kota Ambon Selama Pandemi COVID-19 - Sambonu, Geovani; Jesajas, Heryanus; Rehatta, Lea M (Tropical Small Island Agriculture Management, 2023)
The objective of the research was to investigate the resilience capability of broiler farmers who were affected by the COVID-19 pandemic. The research was arranged using a case study method. The research variables were respondent characteristics, farm characteristics, and respondent perception of impacts of COVID-19 on farm production, marketing, and income changes. The results showed that the COVID-19 pandemic affected farm inputs (feed and Doc) distribution, reduced the number of chickens sold, reduced the income gained by the farmers, and caused an increase in daily consumption costs. Strategies applied by the farmers to withstand included making better use of assets and endowments, namely human, natural, financial, social, and physical capital. It was concluded that the farmers under the contract scheme were more resilient than self-reliant farmers due to larger distribution and marketing channels possessed by enterprises that support the contract farmers.